$10 \exponential{(x)}{2} + 10 x + 8 = 3 \exponential{(x)}{2} - 10 x + 11$

## 共享

10x^{2}+10x+8-3x^{2}=-10x+11

7x^{2}+10x+8=-10x+11

7x^{2}+10x+8+10x=11

7x^{2}+20x+8=11

7x^{2}+20x+8-11=0

7x^{2}+20x-3=0

a+b=20 ab=7\left(-3\right)=-21

-1,21 -3,7

-1+21=20 -3+7=4

a=-1 b=21

\left(7x^{2}-x\right)+\left(21x-3\right)

x\left(7x-1\right)+3\left(7x-1\right)

\left(7x-1\right)\left(x+3\right)

x=\frac{1}{7} x=-3

10x^{2}+10x+8-3x^{2}=-10x+11

7x^{2}+10x+8=-10x+11

7x^{2}+10x+8+10x=11

7x^{2}+20x+8=11

7x^{2}+20x+8-11=0

7x^{2}+20x-3=0

x=\frac{-20±\sqrt{20^{2}-4\times 7\left(-3\right)}}{2\times 7}

x=\frac{-20±\sqrt{400-4\times 7\left(-3\right)}}{2\times 7}

x=\frac{-20±\sqrt{400-28\left(-3\right)}}{2\times 7}

x=\frac{-20±\sqrt{400+84}}{2\times 7}

x=\frac{-20±\sqrt{484}}{2\times 7}

x=\frac{-20±22}{2\times 7}

x=\frac{-20±22}{14}

x=\frac{2}{14}

x=\frac{1}{7}

x=\frac{-42}{14}

x=-3
-42 除以 14。
x=\frac{1}{7} x=-3

10x^{2}+10x+8-3x^{2}=-10x+11

7x^{2}+10x+8=-10x+11

7x^{2}+10x+8+10x=11

7x^{2}+20x+8=11

7x^{2}+20x=11-8

7x^{2}+20x=3

\frac{7x^{2}+20x}{7}=\frac{3}{7}

x^{2}+\frac{20}{7}x=\frac{3}{7}

x^{2}+\frac{20}{7}x+\left(\frac{10}{7}\right)^{2}=\frac{3}{7}+\left(\frac{10}{7}\right)^{2}

x^{2}+\frac{20}{7}x+\frac{100}{49}=\frac{3}{7}+\frac{100}{49}

x^{2}+\frac{20}{7}x+\frac{100}{49}=\frac{121}{49}

\left(x+\frac{10}{7}\right)^{2}=\frac{121}{49}

\sqrt{\left(x+\frac{10}{7}\right)^{2}}=\sqrt{\frac{121}{49}}

x+\frac{10}{7}=\frac{11}{7} x+\frac{10}{7}=-\frac{11}{7}

x=\frac{1}{7} x=-3